The Influence of Product Quality and Price on Purchasing Decisions Mediated by Product Image in The Coffee Powder Processing Industry In The Petang District - I Putu Artha Yoga Widyamukti; I Gede Putu Kawiana; I Wayan Sudiana (International Journal of Economics, Management and Accounting (IJEMA), 2023)
Consumer purchasing decisions are very important in developing the coffee industry in Petang District. For this reason, every company is competing to make its products popular with consumers. The aim of this research is to determine and analyze the influence of product quality and price on purchasing decisions mediated by product image in the Coffee Ground Processing Industry in Petang District. The sample used in this research was 90 people. The research instrument uses a questionnaire and several other data collection methods such as observation, interviews and literature and analysis methods using descriptive analysis and inferential analysis with Structural Equation Model-Partial Least Square (SEM-PLS) analysis. The research results stated that product quality, price and product image had a positive effect on consumer purchasing decisions in the Coffee Ground Processing Industry in Petang District. Quality products and prices have a positive effect on product image in the Coffee Ground Processing Industry in Petang District. Image The product is able to mediate the influence of product quality on consumer purchasing decisions in the Coffee Ground Processing Industry in Petang District. Image The product is able to mediate the influence of price on consumer purchasing decisions in the Coffee Ground Processing Industry in Petang District. The advice that can be given is that the company should pay attention to the length of time it takes to roast the coffee beans so that the resulting coffee powder has a deeper color. The company is re-evaluating the price it sets to be able to attract more consumers. Companies should start using air vacuum in product packaging to maintain product durability. The company tries to make the coffee powder it produces become the main choice of consumers.